LAYANAN ANTAR JEMPUT SEKOLAH SEBAGAI UPAYA UNTUK MENCERDASKAN SUMBER DAYA MANUSIA DI DESA CIASMARA - Hasanah, Tita; Lestari, Lilis; Haris, Abdul; Aida, Siti Nur; Fidhara, Rachmi; Wahyuni, Asri; Fauziah, Hasanatul; Putri, Wulan Purnama (JURNAL SAHID DA'WATII, 2024)
This research aims to determine the needs of the Cibeureum village community, Ciasmara Village in order to improve community education so that the community can be more independent in managing the natural resources available in the surrounding environment. This research method uses a descriptive qualitative approach through data collection derived from SWOT analysis, interviews and observations. The research results show that people basically have the desire and hope that their children can receive the best possible education in order to achieve a better life, but this is hampered by the long distance between school and where they live. So after conducting research, the need for the community to be able to improve their education towards independence in managing natural resources is to provide transportation in the form of school pick-up and drop-off services to facilitate access to education.